Efektivitas Hukum Humaniter Internasional Dalam Kejahatan Perang Pada Konflik Suriah - Annisa Diva Sekartaji; Fatiha Firdaus; Istiqomah Istiqomah; Ida Susilowati (Faculty of Sharia and Law State Islamic University Syarif Hidayatullah Jakarta, 2021)
International Humanitarian Law regulates war in two broad categories: international armed conflict (IAC) and non-international armed conflict (NIAC). The conflict in Syria is an example of a war that has claimed numerous lives. A non-international armed conflict is what it is called when it comes to the crisis in Syria. Violence, both physical and mental, began to take place in Syria. In the aftermath of the political upheaval, a civil war broke out, resulting in war crimes such as murder, kidnapping, bombardment, and rape. The bloodshed and the worst humanitarian disaster in Syria's history were a direct result of this.